Active nematic pumps - Ignasi Vélez-Cerón; Rodrigo C. V. Coelho; Pau Guillamat; Marc Vergés-Vilarrubia; Margarida Telo da Gama; Francesc Sagués; Jordi Ignés-Mullol (Proceedings of the National Academy of Sciences, 2025)
Microfluidics involves the manipulation of flows at the microscale, typically requiring external power sources to generate pressure gradients. Alternatively, harnessing flows from active fluids, which are usually chaotic, has been proposed as a paradigm for the development of micromachines. Here, by combining experimental realizations and simulations, we demonstrate that the addition of triangular-shaped obstacles into an active nematic gel can locally break the fore–aft symmetry of active turbulence and stabilize flow fields with self-pumping capabilities. The proposed strategy has enabled us to generate wall-free and self-powered microfluidic systems capable of both cargo transport and mixing along with the downstream flow. We analyze the performance of these active pumps, both isolated and within cooperative ensembles in terms of their output velocity and hydrostatic pressure buildup. Finally, we demonstrate strategies to incorporate them into specifically designed microfluidic platforms to advantageously tailor the geometry of active flows. Our results reveal possibilities for leveraging the self-organized mechanodynamics of active fluids.